Tropical chronic pancreatitis. Issue 937 (3rd December 2003) - Barman, K K; Premalatha, G; Mohan, V
Abstract : Tropical chronic pancreatitis (TCP) is a juvenile form of chronic calcific non-alcoholic pancreatitis, seen almost exclusively in the developing countries of the tropical world. The classical triad of TCP consists of abdominal pain, steatorrhoea, and diabetes. When diabetes is present, the condition is called fibrocalculous pancreatic diabetes (FCPD) which is thus a later stage of TCP. Some of the distinctive features of TCP are younger age at onset, presence of large intraductal calculi, more aggressive course of the disease, and a high susceptibility to pancreatic cancer. Pancreatic calculi are the hallmark for the diagnosis of TCP and in non-calcific cases ductal dilation on endoscopic retrograde cholangiopancreatography, computed tomography, or ultrasound helps to identify the disease. Diabetes is usually quite severe and of the insulin requiring type, but ketosis is rare. Microvascular complications of diabetes occur as frequently as in type 2 diabetes but macrovascular complications are uncommon. Pancreatic enzyme supplements are used for relief of abdominal pain and reducing the symptoms related to steatorrhoea. Early diagnosis and better control of the endocrine and exocrine dysfunction could help to ensure better survival and improve the prognosis and quality of life of TCP patients.